OUTCOME OF CHILDHOOD ACUTE LYMPHOBLASTIC LEUKAEMIA AFTER INDUCTION THERAPY-3 YEARS EXPERIENCE AT A SINGLE PAEDIATRIC ONCOLOGY CENTRE - Rana, Zulfiqar Ali; Rabbani, Muhammad Waqar; Sheikh, Muhammad Aslam; Khan, Afsheen Asghar (Journal of Ayub Medical College Abbottabad, 2009)
Background: Acute lymphoblastic leukaemia (ALL) is the most common paediatric malignancy. It represents 25% of all childhood cancers and approximately 75% of all cases of childhood leukaemia. A sharp peak of ALL incidence is observed at 2-5 years of age. Objective was to see the bone marrow remission pattern at the end of induction therapy in paediatric ALL patients in our setup. It was a Descriptive case series and conducted at Paediatric Oncology Department, Children Hospital complex Multan from December, 2005 to December, 2008. Methods: Thirty-eight paediatric ALL patients were included in the study. Diagnosis was based on history, examination, blast cells count on peripheral blood film and bone marrow biopsy and immunophenotyping on peripheral blood/bone marrow aspirate. According to UK ALL 2003 protocol all patients were given 4-drug induction therapy, i.e., vincristine, prednisolone/dexamethasone, L-aspiragenase and daunomycin. Bone marrow biopsy was repeated at day 28 of induction therapy and remission pattern was seen. Results: Out of 38 Patients, 26 (68%) were males. Age range was between 2-12 years (Mean 5.4 years). Bone Marrow Biopsy was done in 38 (100%) and Immunophenotyping in 34 (89%) patients. At day 28 of induction therapy, 28 (74%) patients went into complete remission (<5% blast cells in bone marrow), 2 (5%) into partial remission (5-25% blast cells in bone marrow) and 1 (3%) was not in remission (>25% blast cells in the bone marrow). Seven (18%) patient died due to febrile neutropenia and sepsis during the course of induction therapy. Conclusion: ALL in children is curable with effective chemotherapy. Remission can be achieved in most of these patients after induction therapy. However outcome can be improved with effective control of infections. Keywords: Acute Lymphoblastic Leukaemia, Induction Therapy, Remission.